The need and opportunity for donation after circulatory death worldwide. Issue 1 (February 2018) - Manyalich, Martí; Nelson, Helen; Delmonico, Francis L.
Abstract : Purpose of review: The global shortage of organ donors will not be resolved solely by relying on deceased donation following a brain death determination (DBD). Expansion of deceased donation after circulatory death (DCD) will be needed to address the shortfall of organs for transplantation. Approximately 120 000 organ transplants are performed each year; however, the WHO estimates that this number of transplants only resolves 10% of the annual worldwide transplant need. Recent findings: The report addresses the opportunity of DCD expansion by evaluating the DCD potential that is not being realized, the utility of DCD enabling DBD to emerge in some clinical situations, by the effectiveness of a donor registry in achieving DCD, and by the current clinical research of heart, lung, and liver transplantation from DCD. Summary: The future of deceased donation must include DCD and ex-vivo organ repair if the organ shortage is to be reconciled even partially to the ongoing demand. Although the religious and legal impediments have been overcome to determine brain death, the possibility of DCD has not been addressed. A program of DCD is feasible in all countries with transplantation services. The excellent results following kidney and lung transplantation suggest opportunities of heart and liver transplantation should be the focus of needed DCD accomplishment in the near future.